2015
DOI: 10.1080/07347332.2015.1046012
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Sexual Function Measures Administered to Female Cancer Patients: A Systematic Review, 2008–2014

Abstract: Background A systematic review was conducted to identify and characterize self-reported sexual function (SF) measures administered to women with a history of cancer. Methods Using 2009 PRISMA guidelines, we searched electronic bibliographic databases for quantitative studies published January 2008–September 2014 that used a self-reported measure of SF, or a quality of life (QOL) measure that contained at least one item pertaining to SF. Results Of 1,487 articles initially identified, 171 were retained. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 58 publications
2
8
0
1
Order By: Relevance
“…Eighteen distinct measures of sexual well-being concepts were reported, not including sexual health subscales of the quality-of-life scales many authors used as outcome measures. This variability in outcome measures is consistent with the findings of a systematic review of self-reported sexual function measures administered to women with cancer from 2008-2014 (Jeffery et al, 2015).…”
Section: Effectiveness Of the Interventionssupporting
confidence: 83%
“…Eighteen distinct measures of sexual well-being concepts were reported, not including sexual health subscales of the quality-of-life scales many authors used as outcome measures. This variability in outcome measures is consistent with the findings of a systematic review of self-reported sexual function measures administered to women with cancer from 2008-2014 (Jeffery et al, 2015).…”
Section: Effectiveness Of the Interventionssupporting
confidence: 83%
“…A prospective assessment of endometrial and ovarian cancer survivors indicated that the quality of sexual encounters impacts sexual health more than the quantity of encounters (38), further highlighting the complexity involved in assessing the sexual health of this population. Therefore, future studies should include sexuality-based questionnaires to obtain robust information about cancer survivor sexuality (39). Other authors recommend the development of questionnaires that would better account for the lack of or limited sexual activity within the cancer survivor population (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few have been validated in the female cancer patient or survivor populations such as the Female Sexual Function Index (FSFI) [18],and the Sexual Function Questionnaire [19]. More recently, the comprehensive Sexual Function and Satisfaction measure was developed by the National Institutes of Health's Patient-Reported Outcomes Measurement Information System (PROMIS®) Network [**20]. The PROMIS measure, composed of 81 items that span 11 domains [21], was created as a patient-reported outcome measure and may also have potential use in clinical practice.…”
Section: Clinical Inquiry and “The Checklist”mentioning
confidence: 99%